2014
DOI: 10.1073/pnas.1317620111
|View full text |Cite
|
Sign up to set email alerts
|

Probing large conformational rearrangements in wild-type and mutant spectrin using structural mass spectrometry

Abstract: Conformational changes of macromolecular complexes play key mechanistic roles in many biological processes, but large, highly flexible proteins and protein complexes usually cannot be analyzed by crystallography or NMR. Here, structures and conformational changes of the highly flexible, dynamic red cell spectrin and effects of a common mutation that disrupts red cell membranes were elucidated using chemical cross-linking coupled with mass spectrometry. Interconversion of spectrin between closed dimers, open di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…The details of spectrin structure are shown in Figure 3. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] On average, 6 spectrins bind per actin filament, leading to a pseudohexagonal arrangement. 27 Isolated a-and b-spectrin chains bind to each other electrostatically at a pair of nucleation sites formed by repeats near the spectrin tail ( Figure 3A).…”
Section: Spectrinmentioning
confidence: 99%
See 2 more Smart Citations
“…The details of spectrin structure are shown in Figure 3. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] On average, 6 spectrins bind per actin filament, leading to a pseudohexagonal arrangement. 27 Isolated a-and b-spectrin chains bind to each other electrostatically at a pair of nucleation sites formed by repeats near the spectrin tail ( Figure 3A).…”
Section: Spectrinmentioning
confidence: 99%
“…In spectrin ab dimers, the longer a chain folds back on itself, so the a0/b17 repeat interacts with repeat a4 and the a1 and a3 repeats contact each other ( Figure 3A). 13 In the a 2 b 2 -heterotetramers, there are 3 such side-to-side interactions between the longer a chains ( Figure 3C). These lateral interactions, though weak, contribute to self-association.…”
Section: Spectrinmentioning
confidence: 99%
See 1 more Smart Citation
“…This model is morphologically similar to the rotary shadowed electron micrographs of isolated spectrin tetramers [28]. While this crude model resembled rotary shadowed EM images, the absence of lateral association between α and β chains along most of their lengths is inconsistent with chemical crosslinking data from spectrin in solution and on intact red cell membranes [2931]. Further, this concatenation of x-ray crystal structure assumes a gentle left-handed supercoil, while electron microscopy demonstrated that the native quaternary structure of spectrin is a right-handed supercoil [23].…”
Section: Resultsmentioning
confidence: 74%
“…Chemical crosslinking and crosslink identification were performed as previously described [29,30]. Briefly, LC-MS/MS spectra of tryptic digests from mini-spectrin complexes cross-linked with EDC/sulfo-NHS were compared to those from untreated controls to remove background signals and to facilitate targeted acquisition of high-resolution MS/MS spectra.…”
Section: Methodsmentioning
confidence: 99%